The less dead - Mina, Denise (Mulholland Books, Little, Brown and Company, 2020)
Navigating burnout, an unfaithful ex and a relative's recent death, Margo reaches out to her birth family before discovering that her biological mother was murdered years earlier by a killer who begins sending her threatening letters.